Strategi Komunikasi Pemasaran Lasagna Larise Dalam Meningkatkan Penjualan - Irodatul Khasanah (Program Studi Ilmu Komunikasi Fakultas Dakwah dan Komunikasi, UIN Sunan Ampel Surabaya, 2019)
This article discusses how Lasagna Larise's strategy is to increase its sales. This study uses a qualitative-descriptive approach to describe facts and data. The result of this research is Lasagna Larise puts forward appropriate products, quality, and prices, uses vigorous promotions and locations that attract buyers. In addition, they also use advertising and education independently for prospective buyers, especially for resellers who will later resell their products and of course purchase more than retailers. The benefits provided are also attractive to potential buyers. Further education is still being carried out to increase the number of sales and customer loyalty.